Sydenham’s chorea in a family with Huntington’s disease: case report and review of the literature - Santos-Silva, Rita; Corujeira, Susana; Almeida, Ana Filipe; Granja, Sofia; Moura, Cláudia; Azevedo, Inês; Leão, Miguel; Maia, Ana (São Paulo Medical Journal, 2011)
CONTEXT: Sydenham’s chorea affects almost 30% of patients with acute rheumatic fever. It is more frequent in females and is rare in the first decade of life, and genetic vulnerability underlies it. Because of easy access to antibiotics, it is now rare in so-called developed countries. CASE REPORT: A 6-year-old boy with a family history of Huntington’s disease, who was the only child of an unscreened and asymptomatic mother, was brought for a consultation because of migratory arthralgia, depressed mood, and rapid, abrupt and unintentional movements of his right arm and leg, that had evolved over a three-week period. On physical examination, he presented a grade III/VI systolic heart murmur and right-side choreic movements, giving rise to a deficit of active mobilization. Laboratory tests revealed elevated erythrocyte sedimentation rate (63 mm/h), C-reactive protein (25 mg/l) and antistreptolysin O titer (1,824 U/ml). Cardiovascular evaluation showed mild aortic insufficiency, moderate mitral insufficiency and a prolonged PR interval. A clinical diagnosis of Sydenham’s chorea/acute rheumatic fever was made, and therapy consisting of penicillin, haloperidol, captopril and furosemide was instituted, with excellent results. CONCLUSION: In developed countries, Sydenham’s chorea seems forgotten and, because of this, little is known about its clinical course and controversy surrounds the therapeutic options available. This occurrence of rheumatic chorea in a family with Huntington’s disease highlights the importance of the differential diagnosis for the different forms of chorea.